Susan Hefuna: xcultural codes - Gercke, Hans; Hefuna, Susan (3ShRGf Mahfgs; Uthemann, Ernest W. (Heidelberg; Kehrer Verlag, 2004)
Exhibition catalog. Contributions: Negar Azimi, Bryan Biggs, Leonhard Emmerling, Hans Gercke, Rose Issa, Tracy Murinik and Berthold Schmitt.
English; German
Keywords: N4390-5098 Visual Arts. Exhibitions